Wnt signaling in cnidarians - Holstein, Thomas W. (Springer protocols, 2009)
Cnidarians are an ancient group of animals at the base of metazoan evolution. They exhibit a simple body plan with only one well-defined body axis and a small number of cell types. Cnidarians are also well known for their enormous regeneration capacity. Recent work in the freshwater polyp Hydra and in the sea anemone Nematostella has identified an unexpectedly high level of genetic complexity of wnt genes. Canonical Wnt signaling acts in pattern formation and regeneration of Hydra and also in gastrulation and early embryogenesis of Nematostella. Vertebrate-specific Wnt-antagonists were also identified from cnidarians and exhibit similar conserved functions. The simple cnidarian body plan and the now available genomes from Hydra and Nematostella, together with new functional approaches, make these animals an attractive model for studying the basic functions of canonical and non-canonical Wnt signaling.